Pengaruh proses blanching dan penambahan karagenan pada kualitas selai lembaran belimbing wuluh (Averrhoa bilimbi L.) - Devi Rahmah Fauzi; Hapsari Titi Palupi (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
Belimbing wuluh (Averrhoa bilimbi L.) is one of the fruit plants native to Indonesia. Processing of Belimbing wuluh into slice jam is necessary in order to have extended shelf life and to give added value of this fruit. This study aims to determine the effect of blanching and concentration of carrageenan on the quality of belimbing wuluh sheet jam. The method of this research was a randomized block design (RBD) consisting of 2 factors. The first factor were Blanching, (B1) = With Blanching, (B2) = Without Blanching. The second factor was the concentration of carrageenan, carrageenan (K1) = 5%. K2 = 10%. K3 = 15%. The result were analyzed by performed ANOVA using Minitab18 software and continued by the Tukey test. The best treatment was analyzed using the De Garmo Effectiveness Index method. The best treatments found in the B2K2 treatment (without blanching and concentration of carrageenan 10%.) has an average of water content 19.68%; vitamin C 14.51 mg / g; texture 0.50 N / mm2; color L 35.50; a* 13.20; b* 20.80; (organoleptic) texture 3,40 (like); color 3,33 (like); taste 3,47(like); and flavor 3.30 (like).